2021
DOI: 10.5398/tasj.2021.44.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase (SOD) Activity in Cryopreserved Semen of Itik Pinas-Khaki (Anas platyrhynchos L.)

Abstract: Cryopreservation induces oxidative stress on sperm due to an increase in the number of reactive oxygen species (ROS), thereby resulting in decreased sperm quality. ROS's destructive potential is normally counteracted in sperm by their innate antioxidant system consisting of enzymes, which include superoxide dismutase (SOD). This study aimed to assess the quality of semen from Itik Pinas-Khaki (IP-Khaki) drakes that were cryopreserved with either 4.5% DMSO or 7.0% glycerol as cryoprotectant through evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
4
0
1
Order By: Relevance
“…In our study, the ejaculate volume was determined to be 0.68 ± 0.50 ml (Table 2). It was higher than the value given by ANCUELO et al (2021) andCYRIAC et al (2013), but within the range given by WAGNER and PINGEL (1995). These differences could be related to factors such as frequency of ejaculate collection, age, season and feeding.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In our study, the ejaculate volume was determined to be 0.68 ± 0.50 ml (Table 2). It was higher than the value given by ANCUELO et al (2021) andCYRIAC et al (2013), but within the range given by WAGNER and PINGEL (1995). These differences could be related to factors such as frequency of ejaculate collection, age, season and feeding.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies in ducks have found sperm concentrations of 1.5-8.0 x109 sperm/ml (ANCUELO et al, 2021), 3.03 x109 sperm/ml (CYRIAC et al, 2013) and 0.84-1.3x109 sperm/ml (NAHAK et al, 2015), respectively. The collection method, the frequency of collection, the duck species -all these factors can influence sperm concentration.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…SOD is an antioxidant enzyme that is the first and main line against oxidative damage (Kismiati et al, 2021). Superoxide dismutase, which is produced by the liver, is vital in maintaining free radical levels in ROS form in normal settings, preventing an oxidation reaction that might harm the body (Ancuelo et al, 2021). Habashy et al (2019) stated that the SOD mechanism converts oxidative peroxide (H 2 O 2 ) into H 2 O and O 2 in order to protect cells from the oxidative damage caused by H 2 O 2 .…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Os resultados são quantificados medindo a proteção produzida pelos antioxidantes(Cao et al 1993).Inúmeros trabalhos têm utilizado o ORAC para avaliar a capacidade antioxidante total de diferentes amostras(Abraham et al 2021, Ivy et al 2021, Quek et al 2021).4.3. Ensaio da superóxido dismutase SODOs sistemas de defesa intracelulares, que protegem as células de danos induzidos por espécies reativas de oxigênio (ROS), incluem enzimas como a superóxido dismutase (SOD), que catalisa alternadamente a dismutação do radical superóxido (O2 ) em qualquer oxigênio molecular comum (O2) ou peróxido de hidrogênio (H2O2), Ancuelo et al 2021.A metodologia in silico de identificação de moléculas principais contra uma proteína alvo tem sido amplamente utilizada na descoberta de novas abordagensterapêuticas (Singh et al 2021; Hajji et al 2022). da Silva, C.P., et al, 2015.…”
unclassified